2011
DOI: 10.1111/j.1600-0463.2011.02835.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophosmin expression in renal cell carcinoma and oncocytoma

Abstract: The objective of this study was to investigate nucleophosmin/B23 (NPM) expression in renal cell carcinomas (RCC) and renal oncocytomas. The expression of NPM was studied by immunohistochemical methods on 59 RCCs, 9 oncocytomas, and 19 tumour-negative renal tissues. The expression was assessed relative to various clinicopathological variables and histological subtypes, to determine its potential role as a prognostic and diagnostic marker. All tumours showed nuclear staining, and a minority also exhibited cytopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Moreover, NPM was overexpression in thyroid tumors, its dysregulation occurred at protein level and related to an increase of p-Akt level of transformed thyrocytes [ 16 ]. NPM might be a useful immunohistochemical marker for differential diagnosis between oncocytoma and chromophobe renal cell carcinomas (RCCs), and increased nucleolar NPM expression in RCCs appeared to be associated with tumor progression [ 37 ]. All these researches proved the significant value of NPM as a biomarker in the occurrence and progress of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NPM was overexpression in thyroid tumors, its dysregulation occurred at protein level and related to an increase of p-Akt level of transformed thyrocytes [ 16 ]. NPM might be a useful immunohistochemical marker for differential diagnosis between oncocytoma and chromophobe renal cell carcinomas (RCCs), and increased nucleolar NPM expression in RCCs appeared to be associated with tumor progression [ 37 ]. All these researches proved the significant value of NPM as a biomarker in the occurrence and progress of solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that NPM was abnormally overexpressed in MCF-7/MTX cells compared with sensitive cells. Moreover, recent studies have shown that NPM, as non-ribosomal nucleolar phosphoprotein, was high level in a variety of tumors including gastric cancer (28), colon cancer (29), thyroid cancer (30), renal cell carcinoma (31) and even expected as a biomolecular marker for breast cancer (32). In addition, Wang et al (17) found that decreased expression of nucleophosmin/B23 could increase drug sensitivity of adriamycin-resistant Molt-4 leukemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found a correlation between nucleolar nucleophosmin staining and tumor grade. 31 The results from the above-mentioned studies suggest that nucleophosmin expression is highly tumor specific. The lack of differences in nucleophosmin expression between adenocarcinoma and malignant mesothelioma that we found in our study are difficult to explain, but may indicate that this protein is similarly involved in the growth of these two neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin expression has been studied in different cancers including breast, 11 prostate, 18 colon, 19 lung, 20 pancreas, 21 stomach, 22 and testicular tumors, 23 while nucleophosmin has been studied in a wide variety of solid tumors including cancer of the lung, 16 bladder, [24][25] oral cavity, 26 colon, 27 liver, [28][29] thyroid 30 and in renal tumors. 31 Only a few studies have focused on the nucleolus in pulmonary tumors. Xu et al found nucleolar size (inconspicuous vs. prominent) to be associated with lymph node and distant metastases of pulmonary adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%